Communicable Diseases Surveillance: CDI volume 32 issue 3 (2008) - No authors listed (Communicable Diseases Intelligence, 2008)
Includes: Highlights for 2nd quarter, 2008 (bloodborne diseases, gastrointestinal diseases, vaccine preventable diseases, vectorborne diseases); National Notifiable Diseases Surveillance System tables, 1 April to 30 June 2008; Laboratory Serology and Virology Reporting Scheme tables, 1 April to 30 June 2008; Australian Sentinel Practices Research Network, reporting period 1 April to 30 June 2008; Australian childhood immunisation coverage, 1 January to 31 March 2008 cohort, assessed as at 30 June 2008; Gonococcal surveillance, reporting period 1 January to 31 March 2008; HIV and AIDS surveillance, reporting period 1 October to 31 December 2007; National Enteric Pathogens Surveillance System, reporting period 1 April to 30 June 2008; Meningococcal surveillance, reporting period 1 April to 30 June 2008. In the Australian Childhood Immunisation Coverage quarterly report within this document, there is an error of analysis in the calculated percentages of children immunised at 5 years of age (Table 3). This is addressed in an erratum published in CDI vol. 33 (2009). The PDF for the Erratum is included here.